The acute effects of caffeine, creatine, and carbohydrate mouth rinse combined with conditioning activity on subsequent sports performance: a systematic review and Bayesian meta-analysis - Li, Yanfeng; Qiu, Bopeng; Kuai, Hongyan; Huang, Kongyun; Liu, Hengxian; Zhang, Mingyang; Yin, Mingyue; Zhang, Yilin; Deng, Hengzhi; Zhong, Yuming; Kong, Hao; Chen, Jun; et al. (Frontiers in Nutrition, 2025)
BackgroundPost-activation performance enhancement (PAPE) refers to the acute improvement in sports performance following a conditioning activity (CA), commonly used in warm-up protocols and complex training. While CA alone has demonstrated performance benefits, the effects of combining CA-induced PAPE with supplements (e.g., caffeine, creatine, or carbohydrate mouth rinse) remain unclear.ObjectivesThis study was to (i) assess the effects of PAPE combined with supplements on sports performance and fatigue resistance compared to PAPE + placebo, warm-up + supplements, or warm-up alone, and (ii) synthesize direct and indirect evidence on performance outcomes using network meta-analysis.MethodsSearches were conducted across three databases. Eligible studies were randomized controlled or crossover trials involving recreationally active individuals, comparing PAPE combined with supplements to interventions (i.e., PAPE + placebo, warm-up + supplements, or warm-up alone). Outcomes related to sports performance or fatigue were analyzed using a multilevel Bayesian approach incorporating pairwise and multiple (network) comparisons.ResultsTen studies involving 198 participants were included. Current evidence indicates that the probabilities of positive effects (effect size > 0) on sports performance for PAPE combined with supplements compared to PAPE + placebo, warm-up + supplements, warm-up + placebo, and warm-up alone were 90.83, 85.09, 92.29, and 88.10%, respectively. Additionally, PAPE combined with supplements showed an 83.65% probability of superior fatigue resistance compared to PAPE + placebo. Subgroup analysis indicated that plyometric CA (i.e., jump and sprint) combined with supplementation (all were caffeine) was more effective than plyometric CA + PLA (ES = 0.97, >0 probability = 99.79%). Network meta-analysis identified PAPE + caffeine (SURCA = 83.40%) and PAPE + carbohydrate mouth rinse (SURCA = 78.40%) as the most effective interventions for enhancing sports performance, with PAPE + caffeine exhibiting a 99.17% probability of positive effect compared to warm-up alone.ConclusionPreliminary evidence suggests that combining caffeine with plyometric CA is the most effective strategy for enhancing sports performance. Although creatine and carbohydrate supplementation alongside CA may provide some benefits, their effects require further investigation due to small sample sizes and potential publication bias. Practically, these findings provide preliminary evidence that consuming 3–6 mg/kg of caffeine approximately 1 h before plyometric CA may maximize performance enhancement.